Getting dirty and coming clean: Sex education and the problem of expertise. Issue 4 (21st October 2021) - Gilbert, Jen
Abstract: This article recounts my experience serving as an expert witness at a Human Rights Tribunal. In 2018–2019, a grade six trans girl, known only as AB, sued the Ontario provincial government in Canada for revoking a progressive sex education curriculum that addressed gender and sexual identity. While working as an advocate for AB, I wrestled with my own relationship to expertise both within the university and beyond its walls. While describing the process of preparing and testifying before the Tribunal, I focus on two points of tension. First, I draw on Irvine's (2014 ) study on "dirty work" to consider the ways sexuality and gender scholars clean up their research to remove the stigma of sex. To be a sexuality and gender expert requires that I negotiate my proximity to the uncertainties of sexuality—a process complicated for the queer researcher. Second, I consider how the curriculum becomes part of this clean-up effort. In controversies surrounding the sex education of children and youth, progressive advocates counter the moralistic and often religious rhetoric of conservative activists by sterilizing the sex education curriculum through discourses of health and well-being. While I recognize the power of this position, I raise questions about how this strategy neglects the ways youth make and remake the curriculum, exceeding the intentions of teachers, parents, and politicians.